The Effectiveness of Jigsaw Learning Model in Teaching Reading Comprehension on Narrative Text - Adib Ahmada (IAI Darussalam, 2019)
Abstract Reading is considered as an important aspect for students because of its valuable benefit in developing knowledge. There are approaches of teaching reading such as top-down, bottom up, and interactive approach. Some studies was conducted in applying interactive strategy such as Jigsaw learning method. For the purpose of teaching narrative text, the researcher try to observe and analyze the effectivenes of Jigsaw learning method by using an experimental research. The study was conducted on the tenth grade students in SMA Darussalam in the academic year 2018/2019. The writer used testing instrument, pre-test and posttest. The result of the data analysis are as follows: (1) the student’s reading comprehension before being taught by using jigsaw learning model is fair, (2) the student’s reading comprehension after being taught by using jigsaw learning model is good, (3) there is significant difference of the reading comprehension for the students before and after being taught by using jigsaw learning model. So, the writer conclude that, teaching reading comprehension using jigsaw learning model is effective in increasing students’ reading comprehension on narrative text.